Efektivitas Program Masyarakat Bersinar (Bersih Dari Narkoba) Pada Kelurahan Melayu Kota Piring - Satriadi Satriadi; Charly Marlinda; Agus Saputra; Arga Aprial Saputra; Nurul Despurnama Sary; Salsabil Nabila Arifin (Jurnal Pengabdian Kepada Masyarakat, 2022)
Drug abuse occurs because of promiscuity and lack of education about the dangers of drug use. The increasing cases of drug abuse that occur in the community make it quite difficult for the government to overcome this. Therefore, the existence of a drug-free or shining program will certainly have an effectiveness that aims to provide education to the community, especially the younger generation about the dangers and impacts of drug abuse. The method used in this program is through socialization activities using participatory methods, lectures and discussions. The process of this socialization activity was in the form of delivering material from the sources of the City National Narcotics Agency and continued with discussion activities. The results of this program are useful for making the younger generation as pioneers of the nation's successor to be clean from drugs.